Some properties of biorthogonal polynomials and their application to Padé approximations - Holub, A. P. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Transformations of biorthogonal polynomials under certain transformations of biorthogonalizable sequences are studied. The obtained result is used to construct Padé approximants of orders [N−1/N], N ℕ, for the functions f(z) = _m = 0^M α _m f(z) - T_m - 1 [f;z] z^m , where f(z) is a function with known Padé approximants of the indicated orders, T_j [f;z] are Taylor polynomials of degreej for the function f(z), and α_ m, M = 1,M are constants.